2016
DOI: 10.1371/journal.pone.0158718
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic Mapping Reveals Broader Role of Vrn-H3 Gene in Root and Shoot Development beyond Heading in Barley

Abstract: The aim of the present study was to dissect the genetic inheritance and interplay of root, shoot and heading attributes for a better understanding of these traits in crop production. For this, we utilized quantitative trait loci (QTL) and candidate gene analysis approach using a second filial (F2) population originated from a cross between spring cultivar Cheri and wild barley accession ICB181160. The F2 population comprising 182 plants was phenotyped for root dry weight (RDW), root volume (RV), root length (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
2
9
1
Order By: Relevance
“…Moreover, QTLs associated with RSD and RSA ( qRSD2 , Chr 2H, 18.91 cM; qRSD3 , Chr2H, 56.52 cM; qRSA4 , Chr 2H, 58.92 cM) were located in close proximity to the genes Ppd-H1 (Chr 2H,19.9 cM) and HvCEN (Chr 2H, 58.0 cM) that play a central role in regulating flowering time in barley (Turner et al, 2005; Comadran et al, 2012). In accordance, Arifuzzaman et al (2016) also reported that the heading date gene Vrn-H3 significantly associated with shoot and root biomass, although in our panel no QTL was detected in its vicinity. We assume that selection and breeding may have indirectly selected for root traits when selecting for favorable flowering time and high grain yield.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, QTLs associated with RSD and RSA ( qRSD2 , Chr 2H, 18.91 cM; qRSD3 , Chr2H, 56.52 cM; qRSA4 , Chr 2H, 58.92 cM) were located in close proximity to the genes Ppd-H1 (Chr 2H,19.9 cM) and HvCEN (Chr 2H, 58.0 cM) that play a central role in regulating flowering time in barley (Turner et al, 2005; Comadran et al, 2012). In accordance, Arifuzzaman et al (2016) also reported that the heading date gene Vrn-H3 significantly associated with shoot and root biomass, although in our panel no QTL was detected in its vicinity. We assume that selection and breeding may have indirectly selected for root traits when selecting for favorable flowering time and high grain yield.…”
Section: Discussionsupporting
confidence: 90%
“…A more vigorous root system, including longer roots together with a high variation of root traits, was in fact reported for several other wild barley accessions from the Middle East (Arifuzzaman et al, ; ; Naz et al, ; Naz, Arifuzzaman, Muzammil, Pillen, & Léon, ). During breeding programs in the last decades, the focus was largely on increasing aboveground traits, such as yield and grain filling, rather than their root growth (Koevoets, Venema, Elzenga, & Testerink, ).…”
Section: Discussionsupporting
confidence: 52%
“…VERNALIZATION1 ( Vrn1 ), a key regulator of flowering time in cereals, was also involved in root architecture in wheat and barley 61 . QTLs for root traits were also detected in barley in the vicinity of Vrn1 62,63 .…”
Section: Discussionmentioning
confidence: 93%